Excellent Service in Consumers Perspective: A Qualitative Study on Purchase Decisions in the Digital Age - Rahmah, Zulia; Purnamasari, Pupung (ProBisnis : Jurnal Manajemen, 2025)
This study aims to explore how service excellence influences consumer purchasing decisions in the digital era. Using a descriptive qualitative approach, this research involved in-depth interviews with consumers who have transacted through digital platforms such as marketplaces and social media. The findings indicate that consumers perceive service excellence as an important factor in their purchasing decisions. Fast, responsive, and informative services create a positive experience that encourages loyalty and repeat purchases. Furthermore, in today’s digital age, good service interactions not only enhance customer satisfaction but also influence brand perception and reputation on social media. This study concludes that service excellence impacts not only the initial purchasing decision but also the long-term relationship between consumers and companies.